Pengaruh Pengembangan Karir, Komunikasi dan Motivasi Kerja Terhadap Kinerja Pegawai Negeri Sipil pada Dinas Kesehatan Kabupaten Rembang - Saputri Fajar Nur Rochmahwati; Muhammad Tahwin (Pusat Riset dan Inovasi Nasional, 2026)
As a local government institution, the Rembang Regency Health Office plays a role in managing and implementing public health services for the residents of Rembang Regency. The Rembang Regency Health Office is located at Jl. Kartini No. 9, Rembang, Central Java 59215, which has the task of maintaining public health, starting from counseling on healthy lifestyles, disease control, to providing health services at community health centers. Judging from the phenomenon of the still high infant mortality rate, malnutrition, and stunting in Rembang Regency caused by limited access to health care, low awareness of pregnant women, and a lack of midwives and nutritionists. This condition indicates the need to improve the equality of health services, counseling for pregnant women, and the addition of health workers. The purpose of this study was to analyze the relationship between career development, communication, and work motivation with the performance of employees of the Rembang Regency Health Office. This study used a quantitative approach with a research population of 104 employees, and a sampling technique in the form of saturated samples, so that the entire population became respondents. Data collection was conducted using a questionnaire instrument designed based on indicators of career development, communication, work motivation, and employee performance. The analysis method used was multiple linear regression. The research findings indicate that career development and work motivation have a positive and significant effect on employee performance, while communication has a positive but insignificant effect. Together, these three independent variables explain 46.7% of the variation in employee performance at the Rembang Regency Health Office. Therefore, efforts to improve aspects of career development, communication, and work motivation have the potential to improve employee performance.